ANALISIS KEBIJAKAN PEYEDIAAN LAHAN HUTAN TANAMAN INDUSTRI - Epi Syahadat; Sylviani Sylviani (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2014)
Policy analysis on providing land for industrial forest plantation is a review of the rules in the provision of land for industrial forest plantation development, legal basis, as well as efforts made by the government to provide land to the legality IUPHHK permit holders to manage a production forest area. In general the purpose of this study is to review the policy of plantation land supply, and in particular to examine: 1) the policy of forest land allocation and distribution; 2) the provision of licensing procedures and requirements of forest crops; 3) implementation gap in forest plantation area supply regulations. The study results showed that there are no policy gap in providing area for industrial forest plantation. The local government follows the mechanism specified by the forestry regulation stated in P.19/2007 Jo P.11/2008 (HTI). IUPHHK permitting process through the mechanism of an application to the Forestry Minister has not been effective and efficient due to: 1) the absence of standard provisions regarding the cost of the permit application process; 2) there is no synchronize between P.63/2008 with article 5 (letters f and g) in P.11/2008 regarding the request of recommendation to the governor.